2015
DOI: 10.1515/revneuro-2014-0082
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic associations of leukoaraiosis indicate pathophysiological mechanisms in white matter lesions etiology

Abstract: AbstractLeukoaraiosis (LA), also called white matter lesions (WMLs) and white matter hyperintensities (WMHs), is a frequent neuroimaging finding commonly seen on magnetic resonance imaging brain scans of elderly people with prevalence ranging from 50% to 100%. Although it remains asymptomatic, LA is not considered to be benign, and it is showed to be related to a host of poor clinical outcomes and increases the risk of disability, dementia, depression, stroke, and the overall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 119 publications
(168 reference statements)
0
24
1
Order By: Relevance
“…These factors are included in vascular risk measures such as the Framingham score used in this study. A genetic component may be involved in cases where evidence of CVD is lacking[2731]. …”
Section: Discussionmentioning
confidence: 99%
“…These factors are included in vascular risk measures such as the Framingham score used in this study. A genetic component may be involved in cases where evidence of CVD is lacking[2731]. …”
Section: Discussionmentioning
confidence: 99%
“…The axonal loss may compromise the barrier function and then the water will increase in tissues, leading to the changes in DTI-related parameters. [15] These characteristic changes in DTI are helpful for the early identification of brain lesions, disease monitoring, and evaluation of therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the NDRG1 gene located on chromosome 8q24 was hypermethylated (the cytoplasmic protein encoded by this gene is involved in the protection of the myelin sheath in the peripheral nervous system, cell differentiation, tumor metastasis and hypoxia, inflammatory response, etc.) and the BRUNOL4 gene or the CELF4 gene (chromosome 18q12, BRUNO-like 4 protein involved in mRNA stabilization) was hypomethylated compared to the control group with a normal neuroimaging picture [111].…”
Section: Dna Methylationmentioning
confidence: 89%
“…A study of the role of microRNA in the development of leukoaraiosis in CMA [111] revealed eight differentially expressed microRNAs associated with the regulation of pathogenetic gene activity and the molecular mechanisms of leukoaraiosis. It should be noted that the significance of these putative pathogenetic genes was confirmed by the results of GWAS (TRIM65, ACOX1), searches for candidate genes (AGTR2, MTH-FR, BDNF, MMP3, MMP13), gene expression profiles (CCR5, IL6, MAF, CALM1, COL24A1, EPHB2, MAP1B, CYB5A, CDC6, CTSC), and epigenetic studies (HLA-DQA1, TGFBR3, CD80, WDR41, RNF39, KIAA1199, AAK1).…”
Section: Microrna Regulationmentioning
confidence: 99%
See 1 more Smart Citation